Rhus verniciflua leaf extract suppresses obesity in high-fat diet-induced obese mice - Suruga, Kohei (Food Nutr Res, 2019)
BACKGROUND: Obesity is a serious health problem in the world. We thought that the activity and safety of natural plants and/or foods are very important in the management of therapy for obesity. Rhus verniciflua (R. verniciflua) is also known as lacquer tree in Japan and Korea, and it is consumed as food ingredients and/or traditional herbal medicine. We prepared an extract from R. verniciflua leaves (Rv-PEM01-99) to develop a new functional food material and/or nutritional supplements. OBJECTIVE: This study evaluated the anti-obesity effects of the Rv-PEM01-99 in high-fat diet (HFD)-induced obese mice. DESIGN: Six-week-old male C57BL/6J mice were divided into three groups: group I (HFD group), group II (HFD + 1% Rv-PEM01-99 group), and group III (HFD + 2% Rv-PEM01-99 group). Throughout the 56-day treatment period, body weights of these mice were checked twice a week. After 56 days, blood biochemical analyses were performed. RESULTS: In animal studies, no death or abnormalities in food consumption were observed between groups I, II, and III. Body weight gain in the groups administered Rv-PEM01-99 was less than that in group I. In particular, body weight gain in group III was significantly less than that in group I after 52 days of Rv-PEM01-99 administration. In addition, intra-abdominal fat and leptin levels in group III were significantly lower than those in group I. HPLC and LC/MS analysis showed a quercetin derivative as an active compound in Rv-PEM01-99. CONCLUSION: Rv-PEM01-99, containing a quercetin derivative, showed anti-obesity effect in HFD-fed mice. It could therefore be useful as food material and/or nutritional supplement for management of obesity.